2018
DOI: 10.2147/idr.s163293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant Gram-negative pathogens isolated from febrile neutropenic cancer patients with bloodstream infections in Egypt and new synergistic antibiotic combinations

Abstract: IntroductionBloodstream infections with multidrug-resistant (MDR) Gram-negative bacteria (GNB) are among the most frequent complications in immunocompromised cancer patients because of their considerable morbidity and mortality. Several guidelines on antimicrobial therapy have addressed empirical treatment for such serious infections; however, the emergence of microbial resistance has become a significant problem worldwide.Materials and methodsIn this study, starting from November 2015 to October 2016, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
39
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
(35 reference statements)
10
39
3
Order By: Relevance
“…E. coli and Salmonella commonly proliferate in the blood cultures of hospitalized cancer patients with fever [31]. Some strains of E. coli particularly in immunocompromised cancer patients have been linked to potentially severe and life-threatening infections such as UTI [32], both acute and chronic diarrhea (e.g., Enteropathogenic and enterohaemorrhagic E. coli diarrhea [33], or bloodstream infections) [34]. For example, one study (using real-time PCR to quantify bacteria) observed that the microflora composition of the majority of patients experiencing chemotherapy-induced diarrhea showed increase in E. coli and a decrease in Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli and Salmonella commonly proliferate in the blood cultures of hospitalized cancer patients with fever [31]. Some strains of E. coli particularly in immunocompromised cancer patients have been linked to potentially severe and life-threatening infections such as UTI [32], both acute and chronic diarrhea (e.g., Enteropathogenic and enterohaemorrhagic E. coli diarrhea [33], or bloodstream infections) [34]. For example, one study (using real-time PCR to quantify bacteria) observed that the microflora composition of the majority of patients experiencing chemotherapy-induced diarrhea showed increase in E. coli and a decrease in Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, out of the 342 GNB; 188 (54.9%) isolates were MDR which is in accordance with previous studies and imposes weak infection control strategies. 26 , 27 Despite the fact that the antibiogram analysis of recovered GNB is raising concerns, yet, the overall sensitivity patterns of amikacin, doxycycline and tigecycline ranging from 70% to 85% rise as a promising hope.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the development of intensive chemotherapy protocols and interventional procedures have resulted a serious increase in cure rates of the patients, while immunosuppression caused by these treatments also enhances incidence rates of infection. 1 , 2 The relationship between fever and infection in neutropenic patients was defined during the 1960s. Initially, this rarely encountered relationship was described as a serious clinical entity after more widespread and intensive use of cytotoxic drugs and its treatment was started thanks to developed guidelines.…”
mentioning
confidence: 99%
“…The body temperature of ≥38.3°C was measured once from the oral or axillary route or body temperature of 38.0-38.2°C persisting for one hour was defined as neutropenic fever. 1 - 4 Since pathogenic agents are frequently of endogenous origin and polymicrobial in neutropenic patients, foci or agents of infection cannot be identified. 7 , 8 …”
mentioning
confidence: 99%